Unconventional hexagonal open Prussian blue analog structures - Jinwen Yin; Jing Wang; Mingzi Sun; Yajie Yang; Jia Lyu; Lei Wang; Xinglong Dong; Chenliang Ye; Haibo Bao; Jun Guo; Bo Chen; Xichen Zhou; et al. (Nature Communications)
Abstract Prussian blue analogs (PBAs), as a classical kind of microporous materials, have attracted substantial interests considering their well-defined framework structures, unique physicochemical properties and low cost. However, PBAs typically adopt cubic structure that features small pore size and low specific surface area, which greatly limits their practical applications in various fields ranging from gas adsorption/separation to energy conversion/storage and biomedical treatments. Here we report the facile and general synthesis of unconventional hexagonal open PBA structures. The obtained hexagonal copper hexacyanocobaltate PBA prisms (H-CuCo) demonstrate large pore size and specific surface area of 12.32 Å and 1273 m2 g− 1, respectively, well exceeding those (5.48 Å and 443 m2 g− 1) of traditional cubic CuCo PBA cubes (C-CuCo). Significantly, H-CuCo exhibits much superior gas uptake capacity over C-CuCo toward carbon dioxide and small hydrocarbon molecules. Mechanism studies reveal that unsaturated Cu sites with planar quadrilateral configurations in H-CuCo enhance the gas adsorption performance.